Translational profile of coding and non-coding RNAs revealed by genome wide profiling of ribosome footprints in grapevine - Zhen, Zhang; Dongying, Fan; Yue, Song; Lipeng, Zhang; Jingjing, Liu; Minying, Liu; Yuanyuan, Xu; Juan, He; Shiren, Song; Yi, Ren; Bin, Han; Chao, Ma (Frontiers in Plant Science, 2023)
Translation is one of the most crucial points for plant growth and morphogenesis. In grapevine (Vitis vinifera L.), many transcripts can be detected by RNA sequencing, while its translation regulation mechanism is still unknown and there is a great number of translation products have not been identified. Here, the ribosome footprint sequencing was carried out to reveal the translational profile of RNAs in the grapevine. 8291 detected proteins are divided into four parts, including the coding, UTR, intron, and intergenic regions, the 26 nt ribosome-protected fragments (RPFs) showed a 3 nt periodic distribution. Furthermore, the predicted proteins are identified and classified by Go analysis. More importantly, 7 heat shock bind proteins could be found which are involved in molecular chaperone DNA J families participating in abiotic stress. These 7 proteins have different expression patterns in grape tissues, one of them was significantly upregulated by heat stress according to bioinformatics research and was identified as DNA JA6. The result of subcellular localization showed that VvDNA JA6 and VvHSP70 were co-located on the cell membrane. So we speculate that DNA JA6 may interact with HSP70. Besides, overexpression of VvDNA JA6 and VvHSP70 not only reduced MDA content, improved antioxidant enzymes activity of superoxide dismutase (SOD), peroxidase (POD) and osmolyte substance proline content but also observed the expression abundance of high-temperature maker gene VvHsfB1, VvHsfB2A, VvHsfC and HSP100. In summary, our study proved that VvDNA JA6 and heat shock protein VvHSP70 play a positive role in response to heat stress. It lays out a foundation for further exploring the balance mechanism between gene expression and protein translation of grapevine in heat stress.